2019
DOI: 10.25186/cs.v14i4.1625
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber and Antioxidant Activity of Gluten-Free Cookies With Coffee Cherry Flour Addition

Abstract: <p>Coffee husk and coffee pulp are by-product of coffee fruit and bean processing, can be considered as potential functional ingredients for food production as coffee cherry flour (CCF).  The CCF contains a lot of carbohydrates, proteins, caffeine, tannins, and polyphenols. In this study, CCF was combined with modified arrowroot starch (MAS) and modified cassava flour (MOCAF) into cookies and improvement on the physical, chemical, and nutraceutical properties of the cookies were studied. The cookies cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 17 publications
2
23
0
3
Order By: Relevance
“…Arrowroot (Maranta arundinacea L.) contains resistant fiber that ferments in the colon and produces SCFA (Short Chain Fatty Acid) (Damat, 2013) the way inulin and oat do, and modified arrowroot starch has high content of resistant starch (RS) (Damat et al, 2019). Hypothetically, combining cryoprotectant application and modified arrowroot starch utilization should be able to let dough lasts longer.…”
Section: Introductionmentioning
confidence: 99%
“…Arrowroot (Maranta arundinacea L.) contains resistant fiber that ferments in the colon and produces SCFA (Short Chain Fatty Acid) (Damat, 2013) the way inulin and oat do, and modified arrowroot starch has high content of resistant starch (RS) (Damat et al, 2019). Hypothetically, combining cryoprotectant application and modified arrowroot starch utilization should be able to let dough lasts longer.…”
Section: Introductionmentioning
confidence: 99%
“…However, coffee has a very complex chemical composition. In addition to caffeine, coffee contains many other substances that might act as antioxidants (Damat et al, 2019;Halvorsen et al, 2002;Moriera et al, 2013;Natella et al, 2007;Suryono et al, 2020) and antiinflammation (Cardenas; Quesada; Medina, 2011; Dewanti et al, 2019;Kempf et al, 2010;Moriera et al, 2013) that might counteract the adverse effect of caffeine. Due to its rich antioxidant and anti-inflammatory content, it has been hypothesized that coffee consumption might be of benefit to cardiovascular health since oxidation and inflammation represent the important mechanisms in coronary artery disease (Rafieian-Kopaei, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Setyobudi et al [28], Mindarti, et al [29] suggested that coffee husks and pulps be transformed into functional food, namely coffee cherry flour (CCF). Damat et al [30] stated that CCF has a positive impact because it increases the dietary fiber and antioxidant activity in cookies made from gluten-free ingredients.…”
Section: Development -Waste Utilizationmentioning
confidence: 99%